The Labour Supply Effect of Education Maintenance Allowance and its Implications for Parental Altruism - Angus J. Holford (Institute for the Study of Labor (IZA), 2015)
Education Maintenance Allowance (EMA) was a UK government cash transfer paid directly to children aged 16-18, in the first two years of post-compulsory full-time education. This paper uses the labour supply effect of EMA to infer the magnitude of the transfer response made by the parent, and so test for the presence of an 'effectively altruistic' head-of-household, who redistributes resources among household members so as to maximise overall welfare. Using data from the Longitudinal Study of Young People in England, an EMA payment of 30 per week is found to reduce teenagers' labour supply by 3 hours per week and probability of employment by 13 percentage points from a base of 43%. We conclude that parents withdraw cash and in-kind transfers from their children to a value of between 22% and 86% of what the child receives in EMA. This means we reject the hypothesis of an effectively altruistic head-of-household, and argue that making this cash transfer directly to the child produces higher child welfare than if the equivalent transfer were made to parents.
Keywords: I38; J22; H53; 330; transfers; altruism; Education Maintenance Allowance; rotten kid; labour supply